Catalytic hydrotreating of bio-oil and evaluation of main noxious emissions of gaseous phase - Rami Doukeh (Nature Portfolio, 2021)
Abstract Bio-oil produced from biomass pyrolysis has the potential to become an alternative renewable fuel. However due to the high content of oxygenated compounds is unsuitable as transportation fuel. The objective of this work is to evaluate the catalytic activity of CoMo /γ-Al2O3-HMS in the hydrotreating process of biomass pyrolysis bio-oil. The prepared catalyst was characterized by different techniques (X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS)) analysis. The experiments were carried out in a flow fixed-bed reactor at the temperature range of 250–320 °C, pressure between 20–40 bar, and LHSV of 3 h-1. The results showed that at mild conditions of 320 °C and 40 bar, the catalyst is very active in the hydrotreating process leading to a decrease of total acid number of hydrotreated bio-oil with almost 89% and bio-oil conversion of 87.23%. In addition, in order to evaluate the harmful emissions resulted from combustion of gaseous phase obtained in the hydrotreating process a chemical modelling algorithm was developed.